Herramientas de meta modelado en arquitectura empresarial : notación gráfica y métodos de análisis (2021)
The purpose of the following document is to study the use of language workbenches (LWB) and domain-specific languages (DSL) in business modeling; likewise, it is proposed to analyze the development of graphic notation and the analysis methods used in business architecture. For this purpose, a case study of the energy sector was proposed, in which Adoxx was used, an open source LWB built by the University of Vienna. In the case studied, the corresponding graphic notation was built and four automated analysis methods were developed, through scripts that are executed by the language workbench